GANDRA PITALOKA: VISUALISASI KISAH CINTA DYAH PITALOKA DALAM KARYA TARI - Dindin Heryadi; Ela Mutiara (Institut Seni Indonesia Yogyakarta, 2020)
Gandra Pitaloka merupakan visualisasi kisah cinta Dyah Pitaloka putri dari Kadipaten Pakuan dengan Prabu Hayam Wuruk raja dari Kerajaan Majapahit dalam kronologi peristiwa perang Bubat dalam karya tari. Gandra berarti wujud dan Pitaloka diambil dari nama tokoh sumber cerita yaitu Citra Resmi Dyah Pitaloka. Judul ini mengandung arti wujud Dyah Pitaloka. Karya tari ini terinspirasi secara auditif dari syair lagu Karembong Koneng yang menceritakan tentang peristiwa Perang Bubat antara kerajaan Majapahit dan Kadipaten Pakuan. Karya ini diwujudkan dalam bentuk koreografi kelompok dengan sembilan orang penari. Tipe penyajian yang digunakan yaitu tipe dramatik, serta disajikan dengan elemen pertunjukan wayang golek sebagai pengantar cerita. Gerak-gerak dasar tari Sunda seperti tumpang tali, lontang, dan capang, serta unsur dasar gerak silat di antaranya bandul, nangkis, dan nyabet digunakan sebagai pijakan dasar dalam proses pencarian gerak. Musik pengiring dalam bentuk instrumen musik elektrik atau MIDI (Musical Instrument Digital Interface) dengan menggunakan laras Salendro, Pelog, dan Madenda. ABSTRACT Gandra Pitaloka dance is a visualization of the love story of Dyah Pitaloka daughter of Kadipaten Pakuan with Hayam Wuruk king of Majapahit Kingdom in the chronology of Bubat war events. Gandra which means form and Pitaloka was taken from the name of the story source of the official image Citra Resmi Dyah Pitaloka. This title contains the meaning of Dyah Pitaloka's form. This dance work is inspired by audio from Karembong Koneng song lyrics. This poem tells about the events of the war Bubat between the kingdom of Majapahit and Kadipaten Pakuan. This work is manifested in the form of group choreography with the composition of nine dancers. The presentation type used is the dramatic type. Basic movements of Sundanese dance such as tumpang tali, lontang, and capang, and elementary motion of silat which is bandul, nangkis, and nyabet used as a foundation in the process of searching motion. This work is accompanied by music in the form of an electric musical instrument or MIDI (Musical Instrument Digital Interface) by using barrel Salendro, Pelog, and Madenda. And presented with elements of wayang golek show as an introduction to the story. The purpose of this choreography creation is to visualize the love story of Dyah Pitaloka with Hayam Wuruk through the development of basic movements of Sunda dance. The benefits of the creation of this work are to provide a creative process creation experience with the development of motion that departs from the basic movements of the dance of Sundanese and silat, as a form of appreciation of the character of a princess from Kadipaten Pakuan existing in West Java.